Analisis Pengaruh Return on Equity terhadap Harga Saham dengan Price to Book Value sebagai Variabel Intervening pada Perusahaan yang Terdaftar di Bursa Efek Indonesia - Indriyani Indriyani; Rosna Lokano; Ecinta Sari Dewi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to analyze the effect of Return on Equity (ROE) on stock prices with Price to Book Value (PBV) as an intervening variable in companies listed on the Indonesia Stock Exchange (IDX). This study uses a quantitative approach with multiple linear regression methods. The sample consists of 64 company financial report data selected through purposive sampling technique. The results showed that ROE has no significant effect on stock prices, with a significance value of 0.511. In contrast, PBV has a positive and significant effect on stock prices, with a significance value of 0.002. Simultaneously, ROE and PBV have a significant effect on stock prices, as indicated by the significance value of the F test of 0.006. However, the R Square value of 0.155 indicates that this model is only able to explain 15.5% of the variation in stock prices, while the rest is influenced by other factors outside the model.